Fatwa antara Makharij Fiqhiyah dan Market Needs: Eklektisisme Pragmatis di balik Fatwa DSN MUI di Indonesia - Sholihin, Muhammad (AL-ISTINBATH : Jurnal Hukum Islam, 2020)
This study seeks to explore the possibility of implementing eclectic-pragmatic reasoning in the DSN-MUI fatwa on Sharia Banking Products. By applying the Ahmed Fekry Ibrahim study model when exploring the eclectic-pragmatic tradition of Islamic law. This study finally succeeded in introducing a thesis that the DSN-MUI fatwa, especially related to Islamic banking products, is full of eclectic-pragmatic reasoning. Â This is also expected to be the novelty of this study. Because previous studies, such as those conducted by Ahmed Fekry Ibrahim did not specifically discuss the eclecticism of Islamic law on the fatwa products of the Indonesian Ulema Council related to Islamic banking products. This can be identified from two things, namely: First, the eclectic-pragmatic reasoning of the DSN MUI Fatwa on Islamic banking products can be traced from the selection of legal arguments that are consistent in primary arguments, but flexible in choosing secondary arguments - the views of cleric. Second, the principle of protection of corporate needs, in this case encouraging the banking industry to respond to market needs, so that fatwas are made in the framework of these interests.